2022
DOI: 10.1111/een.13118
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance regulates foraging behaviour of ants

Abstract: 1. Theory suggests that performance increases with temperature up to an optimization point before rapidly decreasing as an animal approaches its upper thermal limit.Here, we use the red harvester ant, Pogonomyrmex barbatus, to test predictions about how daily temperature fluctuations and thermal tolerance combine to influence one metric of performance-foraging.2. Over 2 years, we tracked 322 foraging trips from 15 colonies in a mixed grass prairie of southwestern Oklahoma. During each trip, we measured surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…As a result, a warmer climate will not impact all ants species equally. For example, it is often observed that ants with cooler optima for traits such as foraging tend to simply behaviorally avoid too warm conditions [64][65][66][67][68]. Our data nonetheless suggests that a substantial part of temperate ant species may reach a tipping point in the 25-30°C range of body temperatures, where the performance of some critical life-history traits might start declining.…”
Section: Discussionmentioning
confidence: 66%
“…As a result, a warmer climate will not impact all ants species equally. For example, it is often observed that ants with cooler optima for traits such as foraging tend to simply behaviorally avoid too warm conditions [64][65][66][67][68]. Our data nonetheless suggests that a substantial part of temperate ant species may reach a tipping point in the 25-30°C range of body temperatures, where the performance of some critical life-history traits might start declining.…”
Section: Discussionmentioning
confidence: 66%
“…This may be explained by a relationship between CT max and foraging temperature. Whereas most ant species forage at temperatures far from their physiological limits (i.e., they are thermally risk adverse), some do collect rich food resources at temperatures close to their CT max (Cerdá et al, 1998; Roeder et al, 2022). It is possible that the two more heat‐intolerant study species have CT max values that are similar to the temperatures at which they most commonly forage, which means that an increase in CT max could allow them to forage over longer windows of time (Cerdá et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of climate change that predicts an increase of mean global temperature may be important for the studied community (Parr & Bishop 2022). Considering that the thermal tolerances of species seems to be very linked to the current environmental temperatures, physiological limitations may impose an additional challenge for nocturnal ectotherms facing a rapidly warming planet (Roeder et al 2022). Arnan et al (2015), studying environments in the Mediterranean that present little seasonality, found that individuals within ant communities in these regions had similar thermal preferences among themselves.…”
Section: Discussionmentioning
confidence: 99%